Leveraging Technology for Vestibular Assessment and Rehabilitation in the Operational Environment: A Scoping Review - Carrie W. Hoppes; Karen H. Lambert; Susan L. Whitney; Isaac D. Erbele; Carlos R. Esquivel; Tony T. Yuan (Bioengineering, 2024)
Introduction: The vestibular system, essential for gaze and postural stability, can be damaged by threats on the battlefield. Technology can aid in vestibular assessment and rehabilitation; however, not all devices are conducive to the delivery of healthcare in an austere setting. This scoping review aimed to examine the literature for technologies that can be utilized for vestibular assessment and rehabilitation in operational environments. Materials and Methods: A comprehensive search of PubMed was performed. Articles were included if they related to central or peripheral vestibular disorders, addressed assessment or rehabilitation, leveraged technology, and were written in English. Articles were excluded if they discussed health conditions other than vestibular disorders, focused on devices or techniques not conducive to the operational environment, or were written in a language other than English. Results: Our search strategy yielded 32 articles: 8 articles met our inclusion and exclusion criteria whereas the other 24 articles were rejected. Discussion: There is untapped potential for leveraging technology for vestibular assessment and rehabilitation in the operational environment. Few studies were found in the peer-reviewed literature that described the application of technology to improve the identification of central and/or peripheral vestibular system impairments; triage of acutely injured patients; diagnosis; delivery and monitoring of rehabilitation; and determination of readiness for return to duty. Conclusions: This scoping review highlighted technology for vestibular assessment and rehabilitation feasible for use in an austere setting. Such technology may be leveraged for prevention; monitoring exposure to mechanisms of injury; vestibular-ocular motor evaluation; assessment, treatment, and monitoring of rehabilitation progress; and return-to-duty determination after vestibular injury. Future Directions: The future of vestibular assessment and rehabilitation may be shaped by austere manufacturing and 3D printing; artificial intelligence; drug delivery in combination with vestibular implantation; organ-on-chip and organoids; cell and gene therapy; and bioprinting.